Identifying Factors Impacting the Self-concept (SC) and Self-esteem (SE) of Visually Impaired Persons - Fatima, Iqra; Ashraf, Samina; Jahan, Musarrat (Pakistan Journal of Humanities and Social Sciences, 2022)
The current study was aimed at identifying the factors impacting the self-concept and self-esteem of persons with visual impairment. A factorial research design was followed to carry out the study. 75 visually impaired persons were selected as the sample of study from the public and private special schools of Lahore. Robson SCQ and Rosenberg SES were used as assessment tools to measure SC and SE respectively. Data were analyzed through SPSS version 21. From the results of the study, no difference on the basis of gender or type of disability was revealed. However, a statistically significant difference was observed in the SC and SE of visually impaired persons based on age, academic grade, residential area, and support and affection provided by the family. Results of regression analysis showed that all the demographics predict the SC and SE Age, family support, residential area, and academic grade were concluded as the major factors of SC and SE among visually challenged people. The study recommended qualitative research on the study variables to investigate the underlying reasons for the impact of explored factors and to discover more factors impacting the SC and SE of visually impaired persons.